Implementation of the ITE Law and Democracy in Civil Space - Indara, Rona; Ternando, Albi (International Journal of Educational Research Excellence (IJERE), 2024)
The implementation of the ITE Law in general has not been implemented optimally , because the general public's understanding of the ITE Law is still imperfect, including community activities in cyberspace . Activities in cyberspace cannot be separated from human factors and their legal consequences also intersect with humans in society who are in the physical world, therefore the idea emerged about the need for legal rules to regulate activities in cyberspace. The word "Democracy" comes from two words, namely demos which means people, and kratos/cratein which means government, so it can be interpreted as people's government, or what we know better as government of the people, by the people and for the people. This research uses an explanatory type , namely research that explains the implementation of the ITE Law and democracy in cyberspace. From the results of the research that has been carried out, through the process of filling out questionnaires and interview results, it can be concluded that the implementation of the ITE Law in Indonesia is related to democracy in the moderate category